Stategi Manajemen BK Dalam Meningkatkan Kualitas Belajar Peserta Didik - Amirah, Nadiratul; Y, Yarmis; N, Neviyarni (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The primary goal of education is to improve the quality of student learning. This is not solely dependent on academics but also involves their psychological, social, and emotional well-being. This is where guidance and counseling services play a crucial role, helping students overcome learning barriers and optimally develop their potential. This article aims to discuss the importance of managing guidance and counseling services to improve the quality of student learning in schools. This research utilizes a literature review method through a search of relevant books, journals, and scientific articles. The study's findings indicate that effective guidance and counseling management must be implemented through the functions of planning, organizing, implementing, monitoring, and evaluating programs. Regularly managing these services supports the creation of a conducive learning environment, increases student motivation, and strengthens their social and emotional skills. Furthermore, guidance and counseling services have been shown to contribute significantly to improving student learning outcomes and personal development. Therefore, a structured and professional approach to managing guidance and counseling is a crucial foundation for efforts to improve learning quality and achieve comprehensive educational goals.